Self-selection into teamwork: A theoretical and experimental analysis - Agnes Stribeck; Kerstin Pull (Verein für Socialpolitik, 2010)
We analyze self-selection decisions regarding teamwork both theoretically and empirically. While we focus on individual talent, we also investigate the effects of team tasks, individual teamwork skills, and expectations concerning the talent and teamwork skills of potential teammates as further determinants in the self-selection process. Putting our hypotheses derived from a basic self-selection model in dialogue with original data from a real-task laboratory experiment, we are able to show that it is the less talented who find teamwork appealing but that individual teamwork skills and expectations concerning the talent of potential teammates might compensate for this adverse effect.
Keywords: C91; M12; L22; 330